TANGGUNG JAWAB PUSKESMAS TERHADAP PEMANTAUAN PASIEN ISOLASI MANDIRI DALAM PENCEGAHAN DAN PENGENDALIAN PENYEBARAN COVID-19 - Monika Fatma Aulianita; Anggraeni Endah Kusumaningrum (Badan Penerbit STIEPARI Press, 2022)
Early handling of COVID-19 disease was more focused on hospitals, but with the continuous increase in cases and the number of referral hospitals for COVID-19, it continued to increase, even to the point where an emergency hospital was established, so that the responsibility of the Puskesmas was needed as the spearhead of existing health services. in Indonesia. The existence of several obstacles in the responsibilities of the Puskesmas in helping to handle the spread of COVID-19 requires the attention and sincerity of all parties to make improvements so that the Puskesmas can implement health policies to achieve health development goals in their working areas, especially during this pandemic. The formulation of the problems in this study are (1) What is the responsibility of the Community Health Center for Monitoring Self-Isolation Patients in Preventing and Controlling the Spread of Covid-19? (2) What are the obstacles and solutions for the responsibility of the Community Health Center for Monitoring Self-Isolation Patients in Preventing and Controlling the Spread of Covid-19? The research method used in this research is empirical juridical. Data comes from primary data and secondary data. Data were collected by interviews and literature study, data were analyzed using qualitative analysis. The results of this study (1) Puskesmas have responsibility for monitoring self-isolation patients in preventing and controlling the spread of Covid-19 to ensure the health of the community around their area (2) There are obstacles to the responsibility of puskesmas towards monitoring patients in self-isolation in preventing and controlling the spread of Covid-19 19.